The Mediating Role Of Career Development on The Relationship Between Performance Evaluation and Training Management Toward Job Satisfaction - Waaritsa, Abid Khoiril; Susila, Ihwan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of performance evaluation and training management on job satisfaction mediated by career development among Tenggir Park employees. Using a quantitative approach, data were collected through structured questionnaires distributed online to respondents aged 20–35 years in the Soloraya region. The sample was determined using purposive sampling, and data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS 4 software. The research model included performance evaluation and training management as independent variables, career development as a mediating variable, and job satisfaction as the dependent variable. The measurement model was assessed through validity and reliability testing, while the structural model evaluated the relationships among constructs using R² and Q² values. The results show that both performance evaluation and training management have a positive and significant effect on career development and job satisfaction. Furthermore, career development positively and significantly influences job satisfaction and mediates the relationship between performance evaluation, training management, and job satisfaction. These findings indicate that effective performance evaluation and well-managed training programs enhance employees’ career development and overall job satisfaction.